Perspectives on the evolution of animal dancing: a case study of manakins. (December 2015) - Fuxjager, Matthew J; Schlinger, Barney A
Highlights: Males of many manakin species perform physically elaborate courtship displays. Courtship of male golden-collared manakins is androgen-dependent. Androgen receptors are expressed in particular abundance in skeletal muscles. AR expression levels in skeletal muscle predict complexity of male courtship. Selection for elevated muscle AR underlies the evolution of complex male courtship behavior. Abstract : Elaborate physical courtship displays of many male vertebrates require extensive neuromuscular coordination dependent on hormonal activation. How neuromuscular systems evolve to perform essential natural behaviors as well as specialized behaviors required for courtship is poorly understood. We have explored neural, endocrine and muscular adaptations underlying the complex courtship displays of male golden-collared manakins, a bird of neotropical forests. We find that in addition to unique androgen-sensitivity in brain and spinal cord, these birds evolved increased expression of androgen-receptors (AR) in their skeletal musculature. Our evidence from studies of this species and others indicates that selection for elevated skeletal muscle AR expression forms the basis for the evolution of physically elaborate courtship displays.